2020
DOI: 10.1002/mrm.28543
|View full text |Cite
|
Sign up to set email alerts
|

Myelin water imaging depends on white matter fiber orientation in the human brain

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 63 publications
(147 reference statements)
3
68
0
Order By: Relevance
“…Clearly, the resulting pool size will vary depending on how this threshold, which will be field strength dependent, is set. MWI ignores any differential weighting that might be present, for example due to compartment-specific T 1 times ( Birkl et al, 2020 ). For software available for fitting such models, see e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the resulting pool size will vary depending on how this threshold, which will be field strength dependent, is set. MWI ignores any differential weighting that might be present, for example due to compartment-specific T 1 times ( Birkl et al, 2020 ). For software available for fitting such models, see e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has recently been shown that MWF depends on iron content ( Birkl et al, 2019 ), the orientation of fibres with respect to the external magnetic field and on the TR used ( Birkl et al, 2020 ) and exact processing details ( Wiggermann et al, 2020 ). Sensitivity to B 0 inhomogeneity can also bias model fits as can phase errors caused by physiological effects, such as breathing, eddy currents ( Nam et al, 2015a ) and motion, which distorts the decay ( Magerkurth et al, 2011 ).…”
Section: Challenges For Aggregated G-ratio Mappingmentioning
confidence: 99%
“…This highlights the value in characterizing healthy brain MWF and IET2 values across a wide range of ages, as provided by our atlas. Future study could combine MWI data with diffusion models to correct some of the effect of orientation on T 2 relaxation values, and subsequently MWF and IET2 values 40 . Kumar et al have developed an analysis approach using 3D spatial correlations to improve robustness to the spatial and temporal noise in MWI data 41 .…”
Section: Mwf Iet2mentioning
confidence: 99%
“…At 7 T, the WM T 1 is approximately 50% longer 39–41 than at 3 T, 42,43 thus extending TR reduced T 1 ‐weighting at 7 T (Figure 1). Lower short T 2 fractions have been reported with longer TR 44,45 . This observation can be linked to residual T 1 ‐weighting affecting the signal due to multi‐exponential T 1 relaxation of WM as reported by Labadie et al 46 However, as higher M z is available at longer TR , the estimation of the short T 2 component will also be more accurate as SNR is improved 14,20 .…”
Section: Discussionmentioning
confidence: 93%
“…Lower short T 2 fractions have been reported with longer TR. 44,45 This observation can be linked to residual T 1 -weighting affecting the signal due to multiexponential T 1 relaxation of WM as reported by Labadie et al 46 However, as higher M z is available at longer TR, the estimation of the short T 2 component will also be more accurate as SNR is improved. 14,20 Reduced noise levels are advantageous, as positive noise in the first data points of the T 2 decay can falsely enhance short T 2 components.…”
Section: T Sequence Implementation and Potential Consequences Formentioning
confidence: 98%